ANALISYS OF 3 STAR HOTEL PERFORMANCE IN PONTIANAK CITY COMPARATIVE STUDY WITH BALANCED SCORECARD APPROACH - B2041151027, YEKTI PURWO ASIH (Equator Journal of Management and Entrepreneurship (EJME), 2019)
The Balanced Scorecard is an excellent performance measurement tool for measuring business performance today. This tool can measure assets that are factors that can drive the company's advantage in competing and competing with other companies. Measurement of balance scorecard performance is able to detect intangible asset capability such as employee capability, reliable business process, fast and not bureaucratic and highly dynamic and loyal corporate customers. Balanced Scorecard has four fundamental perspectives: learning perspective and employee growth, business process perspective, customer perspective and financial perspective. This research is focused on customer and financial perspectives, as the root of the process towards success for service companies. Assisted by variabels of customer satisfaction in service, service in providing services to customers, downward growth of profit in financial terms. The hypothesis of this study formulated that the customer and financial perspectives affect the financial performance and business processes at 3 Star Hotel Pontianak.This research is descriptive supported by survey method. The number of samples used are 4 4 Star Hotel in Pontianak. Data collected using documentation and interviews. Different test is Wlicoxon Rank Test test done by using SPSS.Â Keywords: Performance, Balanced Scorecard